Dialysis headache: prevalence and clinical presentation in hemodialysis and kidney transplant patients - Gomes, Bruno Teixeira; Costa, Alberto Luis Gomes da; Mazzali, Marilda (Headache Medicine, 2023)
Introduction Headache is a common symptom among hemodialysis patients, with a prevalence around 70%. Dialysis headache is defined according to International Classification of Headache Disorders (ICHD-3) as a headache without specific characteristics, occurring during and caused by hemodialysis that spontaneously disappears within 72 hours after the dialysis session. There is no consensus on trigger factors or physiopathology. Objective To evaluate prevalence, clinical characteristics, and associated factors with dialysis headache. Methods Observational study with quantitative analysis. Study patients were divided into two groups: (HD) 25 hemodialysis patients and (Tx) 25 early post kidney transplant patients. A structured questionnaire was applied to all patients, including Hospital Anxiety and Depression Scale (HADS) and Epworth Sleepiness Scale. Laboratory data, blood pressure and body weight were analyzed before and after one dialysis session. Results: In group HD, eight patients (32%) had diagnosis of dialysis headache, with pulsating headache (n=6, 75%), photophobia (n=6, 75%), phonophobia (n=4, 50%), and nauseas or vomiting (n=6, 75%), with a mean pain score of 7.75 ± 1.58. Headache group had higher scores of anxieties (7.00 ± 3.93 vs. 3.82 ± 3.23, p=0.03) and sleepiness (9.13 ± 3.94 vs. 4.76 ± 3.85, p=0.01), lower levels of serum calcium (p=0.01), and higher systolic (p=0.02) and diastolic (p=0.02) blood pressure pre dialysis. In group Tx, five patients (20%) reported dialysis headache, with pulsating headache (n=4, 80%), nauseas or vomiting (n=4, 80%), with a mean pain score of 8.0 ± 1.41. Headache group had a higher score of sleepiness (9.20 ± 4.32 vs. 4.80 ± 4.51, p=0.029) and were younger (38.93 ± 14.43 vs. 54.02 ± 8.31, p=0.03). Conclusion Headache is frequent among hemodialysis patients and had similar symptoms of migraine. In this series dialysis headache was associated with higher scores of anxieties and sleepiness, higher blood pressure and lower calcium pre dialysis.